No Evidence That Hyperpnea-Based Respiratory Muscle Training Affects Indexes of Cardiovascular Health in Young Healthy Adults - Beltrami, Fernando G.; Mzee, David; Spengler, Christina M. (Frontiers in Physiology, 2020)
Introduction Respiratory muscle training (RMT) benefits athletes, elderly individuals and different patient groups, but the chronic effects of this exercise modality on the cardiovascular system remain unclear. RMT could further be paired with passive lower limb vibration to enhance peripheral blood flow and vascular response. Therefore, this investigation tested to which degree single sessions of RMT with or without added vibration or a 4-week RMT program could result in changes in pulse wave velocity (PWV), blood pressure (systolic, SBP; diastolic, DBP) and other markers of cardiovascular health. Methods Sixteen young and healthy participants (8m/8f) performed – on separate days – 15min of either continuous normocapnic hyperpnea (RMET), sprint-interval-type hyperpnea (RMSIT) or a control session (quiet sitting). Sessions were performed once with and once without passive vibration of the lower limbs. To assess training-induced adaptations, thirty-four young and healthy participants (17m/17f) were measured before and after 4 weeks of RMET (n = 13, 30-min sessions of normocapnic hyperpnea), RMSIT (n = 11, 6x 1min (1 min break) normocapnic hyperpnea with added resistance) or placebo (n = 10). Results SBP was elevated from baseline at 5 min after each RMT session, but returned to baseline levels after 15 min, whereas DBP was unchanged from baseline following RMT. Carotid-femoral PWV (PWVCF) was elevated at 5 and 15 min after RMT compared to baseline (main effect of time, P = 0.001), whereas no changes were seen for carotid-radial PWV (PWVCR) or the PWVCF/PWVCR ratio. Vibration had no effects in any of the interventions. Following the 4-week training period, no differences from the placebo group were seen for SBP (P = 0.686) or DBP (P = 0.233). Likewise, relative changes in PWVCF (P = 0.844), PWVCR (P = 0.815) or the PWVCF/PWVCR ratio (P = 0.389) were not different between the different RMT groups and placebo. Discussion/Conclusion Although 15 min of RMT sessions elicited transient increases in PWVCF and SBP, no changes were detected following 4 weeks of either RMET or RMSIT. Adding passive vibration of the lower limbs during RMT sessions did not provide additional value to the session with regards to vascular responses.